Chronology of Neolithic Sites in the Social and Cultural Space of the Trans-Urals - Vadim S. Mosin (Археология евразийских степей)
The concept of social and cultural space of the Neolithic Trans-Urals describes a historical space, considered in terms of the existing cultural traditions of certain societies in the spatial -temporal framework of the VII–V millennia BC (cal BC). For the Trans-Ural region, 142 radiocarbon dates from 23 sites were analyzed. The purpose of this work was to study the chronological positions of specific sites in the Neolithic. In the process of work, three chronological sections were identified for the sites of the Early Neolithic, with the Koshkino and Kozlovo cultural traditions, age from 6572–6137 cal BC, i.e. middle – last quarter of the VII millennium BC up to 5080–4786 cal BC, i.e. end of the VI – beginning of the V millennium BC. The dates of the Late Neolithic sites represented by the Poludenka and Boborykino traditions are in the range of the end of the VI – middle of the V millennium BC. The Tobol-Ishim interfluve in the Early Neolithic, characterized by the “early” Boborykino tradition of the late VIII – second quarter of the VII millennium BC, was probably included in the social and cultural space of the Neolithic Trans-Urals, as a unique region, the chronology and structure of cultural traditions of which still needs further study.